Evolutionary and ecological role of extracellular contractile injection systems: from threat to weapon - Heiman, Clara Margot; Vacheron, Jordan; Keel, Christoph (Frontiers in Microbiology, 2023)
Contractile injection systems (CISs) are phage tail-related structures that are encoded in many bacterial genomes. These devices encompass the cell-based type VI secretion systems (T6SSs) as well as extracellular CISs (eCISs). The eCISs comprise the R-tailocins produced by various bacterial species as well as related phage tail-like structures such as the antifeeding prophages (Afps) of Serratia entomophila, the Photorhabdus virulence cassettes (PVCs), and the metamorphosis-associated contractile structures (MACs) of Pseudoalteromonas luteoviolacea. These contractile structures are released into the extracellular environment upon suicidal lysis of the producer cell and play important roles in bacterial ecology and evolution. In this review, we specifically portray the eCISs with a focus on the R-tailocins, sketch the history of their discovery and provide insights into their evolution within the bacterial host, their structures and how they are assembled and released. We then highlight ecological and evolutionary roles of eCISs and conceptualize how they can influence and shape bacterial communities. Finally, we point to their potential for biotechnological applications in medicine and agriculture.